Model SERASI sebagai Upaya Meningkatkan Kreativitas dan Kemampuan Menulis di Sekolah Dasar - Anita Inayati; Rizky Amelia (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This classroom action research examines the improvement of students’ creative thinking and writing skills through the implementation of the SERASI learning model in Indonesian language lessons. The identified problem was the low level of both skills due to a less meaningful learning process and limited opportunities for students to develop them. This study employed a qualitative approach and was conducted with 16 fifth-grade students at SDN Pemurus Dalam 2 over four sessions during the second semester of the 2024/2025 academic year. Data were collected through observations of teacher and student activities, assessments of writing and creative thinking skills, as well as written learning tests. The results showed a significant improvement, with creative thinking skills increasing from 42% (less skilled) to 83% (very skilled), and writing skills rising from 42% (less skilled) to 84% (very skilled). These findings indicate that implementing the SERASI model is effective in optimizing both skills and is recommended as an innovative learning alternative at the elementary school level.